The emergence of inclusive growth: Issues, challenges and policy options for Nigeria - Perekunah B. Eregha; Ekundayo P. Mesagan (African Governance and Development Institute (AGDI), 2019)
This study analysed the issues involved in inclusive growth as well as the challenges faced by Nigeria. Issues like economic growth, green growth, inclusive green growth and inclusive growth were discussed in the study. Key determinants of inclusive growth such as human capital investment, job creation, structural transformation, social protection and quality institutions were identified. With regards to Nigeria, it was observed that the country is still far away from realistically being able to achieve inclusive growth as dependency ratio, poverty and depletion of natural capital is very high. Also, health care delivery is very poor and institutional quality is almost non-existent. We therefore recommended that government should strengthen its institutions by allowing every government agency to function independently and in accordance with constitutional provisions. They should also control those activities that cause depletion of natural capital and bring down the incidence of poverty to the barest minimum to ensure that growth becomes inclusive.
Keywords: D31; I32; I38; 330; Inclusive Growth; Green Growth; Institutions; Social Protection; Human Capital